2021
DOI: 10.1021/acsaelm.1c00364
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Texture and Microstructure in a NdFeAs(O,F)/IBAD-MgO Superconducting Thin Film with Superior Critical Current Properties

Abstract: This paper reports the nanoscale texture and microstructure of a high-performance NdFeAs(O,F) superconducting thin film grown by molecular beam epitaxy on a textured MgO/Y 2 O 3 /Hastelloy substrate. The NdFeAs(O,F) film forms a highly textured columnar grain structure by epitaxial growth on the MgO template. Although the film contains stacking faults along the abplane as well as grain boundaries perpendicular to the ab-plane, good superconducting properties are measured: a critical temperature, T c , of 46 K … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In the results, both research groups [43,44] reported that the point pinning dominates at 0.5 T T c , while at T T c 0.5, the dominant mechanism is the surface pinning. Because the comprehensive analysis of → F p (B, T, θ = 0 • ) for NdFeAs(O,F) thin films was reported in [43,44], here, we only presented an analysis for the…”
Section: Pnictide Thin Filmsmentioning
confidence: 86%
See 3 more Smart Citations
“…In the results, both research groups [43,44] reported that the point pinning dominates at 0.5 T T c , while at T T c 0.5, the dominant mechanism is the surface pinning. Because the comprehensive analysis of → F p (B, T, θ = 0 • ) for NdFeAs(O,F) thin films was reported in [43,44], here, we only presented an analysis for the…”
Section: Pnictide Thin Filmsmentioning
confidence: 86%
“…In this section, the analysis was applied for two NdFeAs(O,F) thin films for which raw transport critical current density data, 𝐽 (𝐵, 𝑇, 𝜃 = 0°), were reported by Tarantini et al [43] and Guo et al [44]. Both research groups found that the 𝐹 ⃗ (𝐵, 𝑇, 𝜃 = 0°) data fit to Equation (3) generates unphysical 𝑝(𝑇) and 𝑞(𝑇) values, which was interpreted as a → F p (B, T, θ = 0 • ) curves and data fits to Equation (13) for a MgB 2 thin film deposited on a 6H-SiC single-crystal substrate for the temperature range of 4.2-30 K (a-f).…”
Section: Pnictide Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ga has been used to remove excess fluorine during deposition. Although fine tuning is necessary, parent compound NdFeAsO has been fabricated on a large variety of oxide and fluorine substrates [67], as well as technical substrates [68,69]. Typical growth temperatures are around 800 • C. The growth rate is approximately 0.8-1 nm min −1 .…”
Section: Molecular Beam Epitaxy Mbementioning
confidence: 99%